Efficacy of 1 Versus 3 Days of Intravenous Amikacin as a Prophylaxis for Patients Undergoing Transurethral Resect Prostate: A Prospective Randomized Trail - Abdul Basit Niazi, Rashid Ali, Hira Anis Bumbia, Muhammad Asif, Muhammad Ammar, Haleemullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The goal of the current study was to investigate the safety of a single dose of IV Amikacin given a period of three days as compared to a single dose of one and two days, when used as a surgical prophylactic antibiotic prior to transurethral prostate resection. Study Design: This was a randomized and prospective study conducted at Urology Department of Niazi Medical & Dental College Sargodha for the duration of six-months from May 2022 to October 2022. Methods: There were 300 men who participated in total and had their prostates transurethral resected (TURP). Three groups, A, B, and C, each with 100 participants, were created randomly from among the participants. The participants will either be assigned at random to receive a single dose of Amikacin that complies with recommendations for groups A, B, and C on days 1, 2, and 3. Follow Up until day 30 following surgery, routinely gathered data from TURP will be the end of the study. Within 60 minutes of the incision, all patients received a single dose of prophylactic antibiotics. Results: The Groups A and B had higher rates of significant bacteriuria than Group C, the intention-to-treat analysis determined that this difference was not statistically significant. The results of a per-protocol analysis were similar. (p=0.88; 0.13). This suggests that postoperative bacteriuria poses a significant risk for the emergence of UTI symptoms (p=o.oo2**). Antibacterial drug resistance has a significant relationship with the progression of infectious complications and was associated with a history of diabetes (95% [CI]]: 0.08-3.11, OR=0.33; p=0.01*) and surgical history and ESBL positivity were indicate infection-related issues (95% [CI]: 1.51-1.86, OR=5.1; p=0.023 and 95% [CI]: 2.55-13.1, OR=4.90; p<0.0001***). Conclusions The Amikacin was safe for surgical prophyaxis in single dose until 3 days as compared to 1 and 2 days because of the incidence of postoperative complication such as UTI reduced. It was greater role to decrease antibiotic resistance. Keyword: Bacterial infection, Urinary tract, Antibiotics.